"Pay for Success" Financing and Home‐Based Multicomponent Childhood Asthma Interventions: Modeling Results From the Detroit Medicaid Population. Issue 2 (4th June 2018) - LANTZ, PAULA M.; MILLER, GEORGE; RHYAN, CORWIN N.; ROSENBAUM, SARA; KU, LEIGHTON; IOVAN, SAMANTHA
Abstract : Policy Points: The Pay for Success (PFS) financing approach has potential for scaling the implementation of evidence‐based prevention interventions in Medicaid populations, including a range of multicomponent interventions for childhood asthma that combine home environment risk mitigation with medical case management. Even though this type of intervention is efficacious and cost‐saving among high‐risk children with asthma, the main challenges for implementation in a PFS context include legal and regulatory barriers to capturing federal Medicaid savings and using them as a source of private investor repayment. Federal‐level policy change and guidance are needed to support PFS financing of evidence‐based interventions that would reduce expensive acute care among Medicaid enrollees. Context: Pay for Success has emerged as a potential financing mechanism for innovative and cost‐effective prevention programs. In the PFS model, interventions that provide value to the public sector are implemented with financing from private investors who receive a payout from the government only if the metrics identified in a performance‐based contract are met. In this nascent field, little has been written about the potential for and challenges of PFS initiatives that produce savings and/or value for Medicaid. Methods: In order to elucidate the basic economics of a PFS intervention in a Medicaid population, we modeled the potential impact of an evidence‐based multicomponent childhood asthma intervention among low‐income children enrolled in Medicaid in Detroit. We modeled outcomes and a comparative benefit‐cost analysis in 3 risk‐based target groups: (1) all children with an asthma diagnosis; (2) children with an asthma‐related emergency department visit in the past year; and (3) children with an asthma‐related hospitalization in the past year. Modeling scenarios for each group produced estimates of potential state and federal Medicaid savings for different types or levels of investment, the time frames for savings, and some overarching challenges. Findings: The PFS economics of a home‐based asthma intervention are most viable if it targets children who have already experienced an expensive episode of asthma‐related care. In a 7‐year demonstration, the overall (undiscounted) modeled potential savings for Group 2 were $1.4 million for the federal Medicaid and $634, 000 for the state Medicaid programs, respectively. Targeting children with at least 1 hospitalization in the past year (Group 3) produced estimated potential savings of $2.8 million to federal Medicaid and $1.3 million to state Medicaid. However, current Medicaid rules and regulations pose significant challenges for capturing federal Medicaid savings for PFS payouts. Conclusions: A multicomponent intervention that provides home remediation and medical case management to high‐risk children with asthma has significant potential for PFS financing in urban Medicaid populations. However, there are significant administrative and payment challenges, including the limited ability to capture federal Medicaid savings and to use them as a source of investor repayment. Without some policy reform and clear guidance from the federal government, the financing burden of PFS outcome payments will be on the state Medicaid program or some other state‐level funding source.